Purinergic mechanisms of lateral parabrachial nucleus facilitate sodium depletion-induced NaCl intake - Menezes, Miguel F. [UNESP]; Barbosa, Silas P. [UNESP]; Andrade, Carina A. F. de [UNESP]; Menani, José Vanderlei [UNESP]; De Paula, Patricia M. [UNESP] (Elsevier B.V., 2011)
Purinergic receptors are present in the lateral parabrachial nucleus (LPBN), a pontine structure involved in the control of sodium intake. In the present study, we investigated the effects of alpha,beta-methyleneadenosine 5'-triphosphate (alpha,beta-methylene ATP, selective P2X purinergic agonist) alone or combined with pyridoxalphosphate-6-azophenyl-2',4'-disulfonic acid (PPADS, P2X purinergic antagonist) or suramin (non-selective P2 purinergic antagonist) injected into the LPBN on sodium depletion-induced 1.8% NaCl intake. Male Holtzman rats with stainless steel cannulas implanted into the LPBN were used. Sodium depletion was induced by treating rats with the diuretic furosemide (20 mg/kg of body weight) followed by 24 h of sodium-deficient diet. Bilateral injections of alpha,beta-methylene ATP (2.0 and 4.0 nmol/0.2 mu l) into the LPBN increased sodium depletion-induced 1.8% NaCl intake (25.3 +/- 0.8 and 26.5 +/- 0.9 ml/120 min, respectively, vs. saline: 15.2 +/- 1.3 ml/120 min). PPADS (4 nmol/0.2 mu l) alone into the LPBN did not change 1.8% NaCl intake, however, pretreatment with PPADS into the LPBN abolished the effects of alpha,beta-methylene ATP on 1.8% NaCl intake (16.9 +/- 0.9 ml/120 min). Suramin (2.0 nmol/0.2 mu l) alone into the LPBN reduced sodium depletion-induced 1.8% NaCl intake (5.7 +/- 1.9 ml/120 min, vs. saline: 15.5 +/- 1.1 ml/120 min), without changing 2% sucrose intake or 24 h water deprivation-induced water intake. The combination of suramin and alpha,beta-methylene ATP into the LPBN produced no change of 1.8% NaCl intake (15.2 +/- 1.2 ml/120 min). The results suggest that purinergic P2 receptor activation in the LPBN facilitates NaCl intake, probably by restraining LPBN mechanisms that inhibit sodium intake. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Adenosine 5 '-triphosphate (ATP); Sodium appetite; Suramin; PPADS; alpha,beta-Methylene ATP; P2 purinergic receptors